Safety and efficacy of Avizyme® 1505 (endo‐1, 4‐beta‐xylanase, subtilisin and alpha‐amylase) for all poultry species. (21st February 2020) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kos Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Avizyme ® 1505 is based on three enzyme activities produced by three genetically modified microorganisms: xylanase, subtilisin and amylase produced by Trichoderma reesei, Bacillus subtilis and Bacillus amyloliquefaciens, respectively. It is authorised for use in chickens and turkeys for fattening, ducks and laying hens. This scientific opinion concerns the request for the renewal of the authorisation of the additive for the species/categories for which there is an authorisation, a reduction of the minimum recommended level in turkeys for fattening and the extension of use to all avian species for laying, for fattening, reared for breeding and reared for laying (except for ducks). Based on recent data, uncertainty remains in the characterisation of the production strains and the possible presence in the final product of viable production strains and their DNA. Therefore, the EFSA Panel on Additives and products or Substances used in Animal Feed (FEEDAP) could not confirm the conclusions previously drawn regarding the safety of Avizyme ® 1505 for the target species, consumers, users and environment. This conclusion applies also to the new target species for which a request for an extension of use is made. There was no need for assessing the efficacy of the additive in the context of the renewal of the authorisation for chickens for fattening, ducks and laying hens. The efficacy data previously evaluated allowed the Panel to conclude that the additive has the potential to be efficacious at 187.5 U xylanase, 2, 500 U subtilisin and 250 U amylase/kg complete feed for all avian species for fattening (including turkeys), reared for breeding and reared for laying and 300 U xylanase, 4, 000 U subtilisin and 400 U amylase/kg complete feed in all avian species for laying.